PRACTICAL ANALYSIS OF THE PLACEMENT OF FILTHY ON THE SAME COTTON WOOL IN STACKS AND WAREHOUSES - Turgunov, D.U.; Kabilov , B.Q. (Educational Research in Universal Sciences, 2023)
The article investigated whether raw material moisture is variable when storing cotton raw materials in Garam fields, and the effect of cotton on the degree of distribution of cotton in its layers cross section, depending on the height of the garam area. In this case, additional compaction of cotton under the influence of weight strength from the upper layers to the lower ones and differences in microneedles of cotton fibers have been found.